Reverse Engineering dan Evaluasi Desain pada Komponen V-Plow Conveyor Belt Jenis Bulk Material Handling menggunakan Metode Elemen Hingga - Febriyanto, Febriyanto; Cahyati, Sally (TURBO [Tulisan Riset Berbasis Online], 2025)
This paper discusses reverse engineering and design evaluation of the V-Plow component in conveyor belt systems used for handling bulk materials in the mineral and coal industry. V-Plow functions as a carryback material cleaning tool that can be carried to the bottom of the tail pulley on the conveyor belt. The absence or non-optimality of this tool can cause extreme damage to the tail pulley due to material carryback from the head pulley. This research aims to evaluate and redesign the V-Plow so that it has a more appropriate safety factor compared to the existing design. Design changes also include the addition of springs to improve V-Plow performance. Tests were carried out using SolidWorkss software, and the stress analysis on the belt was calculated physically. The research results show that the existing design has a safety factor that is too large, namely 22.5, which indicates high production costs and over-specification. The redesign succeeded in reducing the safety factor to 6, which is still within safe limits. In accordance with CEMA standards, the optimum tension on the belt is 5 lb/in belt width. By adding a three spring design, the optimal force F = 355.67 N, twisting moment ð‘€=11.3 ð‘ð‘š, torsion spring constant ð¾ ð‘¡ð‘œð‘Ÿð‘ ð‘–ð‘œð‘›=28.577 ð‘ð‘š/ð‘Ÿð‘Žð‘‘, and working angle of the torsion spring ð›¼= 22.63 degrees. The frame weight has also been reduced from +116 kg to +83 kg (28%) through the new design. This research proves that the V-Plow redesign not only increases efficiency but also reduces production costs, making it a more optimal and economical solution for the mineral and coal industry.